The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1111/j.2042-3306.1998.tb05128.x
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of static loading in donkey hoof wall

Abstract: Summary A finite element model of donkey hoof wall was constructed from measurements taken directly from the hoof capsule of the left forefoot. The model was created with a 2 mm mesh and consisted of 11608 nodes. A linear elastic analysis was conducted assuming isotropic material properties in response to a 375 newton (N) load, to simulate static loading. The load was applied to the wall via 400 laminae in order to simulate the way in which the pedal bone is suspended within the donkey hoof capsule. Displaceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Previous FE models of the hoof capsule (wall and sole and frog in some cases) have shown that the general pattern of deformation and displacement of the models are in broad agreement with experimentally derived data (Hinterhofer et al 1997(Hinterhofer et al , 2000Newlyn et al 1998). The models all showed palmar movement of the toe, with abaxial flare of the quarters and heels, as seen in vivo (Lungwitz 1891;Roepstorff et al 2001).…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Previous FE models of the hoof capsule (wall and sole and frog in some cases) have shown that the general pattern of deformation and displacement of the models are in broad agreement with experimentally derived data (Hinterhofer et al 1997(Hinterhofer et al , 2000Newlyn et al 1998). The models all showed palmar movement of the toe, with abaxial flare of the quarters and heels, as seen in vivo (Lungwitz 1891;Roepstorff et al 2001).…”
Section: Introductionsupporting
confidence: 62%
“…The models all showed palmar movement of the toe, with abaxial flare of the quarters and heels, as seen in vivo (Lungwitz 1891;Roepstorff et al 2001). Magnitudes of displacement of specific regions of the wall were also plausible (Newlyn et al 1998). The models used here have been shown to deform and displace accurately (H. L. McClinchey et al, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…This is an important finding when considering corrective farriery based on the position of the distal phalanx within the hoof capsule. During the stance phase, the two main hoof deformations are horizontal spreading of the heels away from each other and bowing‐ in of the dorsal hoof wall . It appears that the load variation induced by a variation in stance alone is not enough to cause change in the position of the distal phalanx.…”
Section: Discussionmentioning
confidence: 99%
“…The finite element method (Newlyn et al 1998;Hinterhofer et al 2001) was presented to simulate mechanics of a donkey and a horse digit model. A different computational distal forelimb model was presented to investigate strains in the flexor tendons (Chan and Lawson 2008), concluding that the high repeatability of the model is an indicator for its sensitivity.…”
Section: Oral Session 3: Measurement Techniques Limb and Trunk Mechamentioning
confidence: 99%